Posterior interosseous neuropathy: Supinator syndrome vs fascicular radial neuropathy - Bäumer, Philipp; Kele, Henrich; Xia, Annie; Weiler, Markus; Schwarz, Daniel; Bendszus, Martin; Pham, Mirko (Neurology, 2016)
Objective: To investigate the spatial pattern of lesion dispersion in posterior interosseous neuropathy syndrome (PINS) by high-resolution magnetic resonance neurography. - Methods: This prospective study was approved by the local ethics committee and written informed consent was obtained from all patients. In 19 patients with PINS and 20 healthy controls, a standardized magnetic resonance neurography protocol at 3-tesla was performed with coverage of the upper arm and elbow (T2-weighted fat-saturated: echo time/repetition time 52/7,020 milliseconds, in-plane resolution 0.27 3 0.27 mm2). Lesion classification of the radial nerve trunk and its deep branch (which becomes the posterior interosseous nerve) was performed by visual rating and additional quantitative analysis of normalized T2 signal of radial nerve voxels. - Results: Of 19 patients with PINS, only 3 (16%) had a focal neuropathy at the entry of the radial nerve deep branch into the supinator muscle at elbow/forearm level. The other 16 (84%) had proximal radial nerve lesions at the upper arm level with a predominant lesion focus 8.3 6 4.6 cm proximal to the humeroradial joint. Most of these lesions (75%) followed a specific somatotopic pattern, involving only those fascicles that would form the posterior interosseous nerve more distally. - Conclusions: PINS is not necessarily caused by focal compression at the supinator muscle but is instead frequently a consequence of partial fascicular lesions of the radial nerve trunk at the upper arm level. Neuroimaging should be considered as a complementary diagnostic method in PINS. Neurology® 2016;87:1884-1891
Gesehen am 23.04.2020